ANALYSIS OF TRANSFLUTHRIN IN HOUSEHOLD PESTICIDE PRODUCTS OF AEROSOL PREPARATION - Warnandi, Alif
Transfluthrin is a biocide compound commonly used as an active ingredient in household pesticide products as part of household products. The aim of this study was to obtain a valid analytical method for determination of transfluthrin in household pesticide products of aerosol preparation and data on the levels of transfluthrin in these products. Transfluthrin analysis was carried out by applying gas chromatography method, starting from testing various validation parameters followed by determination of transfluthrin levels in the sample. The results showed that a suitable gas chromatography system was equipped with a Flame Ionization Detector (FID) detector at 300 ?C, an Rtx-5sil MS column, an injector temperature of 290 ?C, an oven temperature set in a gradient, and the make-up rates of helium, hydrogen, and oxygen gas of respectively 25, 40, and 400 mL/min. The injection volume is 1 µL with an injection split ratio of 1:25 and a test time of 10 minutes. Linearity of the method was achieved in the concentration range of 100 to 500 ?g/mL with the calibration curve equation of Y = 438.21X – 9111.3 and r2 of 0.9983. Limit of detection and Limit of quantification of the method were respectively 28.9 and 72.0 ?g/mL, method precision expressed as Relative Standard Deviation (RSD) of 0.2911 to 3.6396%, and accuracy expressed as a percentage of recovery of 91.4 to 97.7%. Transfluthrin levels in samples were in the range of 553,932.7 – 573,069.8 µg/g. Based on the overall results, it can be concluded that the analytical method for determining transfluthrin levels in household pesticide products of aerosol preparation was successfully obtained.